Pengaruh Konsumsi Alkohol terhadap jumlah Eritrosit dan Hemoglobin Mencit (Mus musculus) - Raudhah Hayatillah; Widie Kemala Hapsari; Syukriah Syukriah (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2021)
Alcohol is an organic compound that is often used in our life. In science research, alcohol is used as a solvent, fuel, and antiseptic. Alcohol if consumed in large quantities has side effects on the body that affect physiologically, one of which is nerve damage, liver and kidney damage, and affects the fetus if consumed by pregnant women. In addition, it is known that alcohol can affect erythrocytes and hemoglobin. In this study, alcohol was given to mice (Mus musculus) to see the effect on the number of erythrocytes and hemoglobin. This study used beer concentrations of 4% and 1% and distilled water as a control. The experimental animals used were 9 mice which would be induced by 1 mL of alcohol for 5 days. The parameters used were the number of erythrocytes and hemoglobin. Data collection was carried out 3 times after 5 days of alcohol induction. The result of this study is that alcohol can reduce the number of erythrocytes and hemoglobin in mice. Decreased erythrocytes and hemoglobin in mice Â have an impact on other body organ damage.